Social struktur och dominans hos hund - Strandner, Johanna (2015)
The dog (Canis lupus familiaris) is the first species ever domesticated. They can develop a close bond towards other dogs, almost like a relationship among siblings, which can be a high valuable resource for good relations and cooperation’s. Dominance in dogs is sometimes used to explain undesired behaviors and explained as a personality trait. Dominance though, is not a trait in a dog or a source for undesired behaviors, but can rather be explained as a relationship between individuals, were one of them receives more submissive signals from the other. A dog’s social status is not permanent and can change in different groups of dogs, because the social status depends on how many submissive interactions the individual receives from others. Older individuals receive more submissive signals and are more often seen in a high social status position, why the social status appears to be related to age. Dominance is most often displayed when a dog returns to the group after being separated, and then receives submissive signals from conspecifics. Interestingly, dominance appears without aggression contrary to what sometimes is used when training dogs showing undesired behaviors such as aggression. When aggression is displayed among dogs, it is because there is competition about recourses such as food. Despite competitive situations, aggression is not a winning strategy. Dogs seem to behave carefully when around individuals expressing agonistic behavior, why aggression is not an advantage. Similar to the dog, the wolf does not have a permanent social status either. In the wolf pack, the breeding pair works as a family mum and dad and nor in this composition aggression has been observed to contain social status. Dogs use almost their entire body when communicating with conspecifics. The ears, nose, body posture, tail, lips and eyes are all parts of their signaling system. But dogs’ morphology can complicate the signaling and receiving of signals between individuals resulting in conflicts between them caused by confusion. ...